Control policy for a subclass of Petri nets without reachability analysis. Issue 8 (1st May 2013) - Liu, GaiYun; Chao, Daniel Yuh; Yu, Fang
Abstract : Traditional maximally permissive deadlock prevention control for flexible manufacturing systems requires costly reachability analysis. It has been a hot race to synthesise optimal controllers to be maximally permissive with fewest monitors. Previous work shows that among all n ‐dependent siphons, only one siphon (whose unmarked state follows some token distribution) needs to be controlled. This greatly simplifies the supervisor synthesis as well as minimises the number of monitors required while making the controlled net maximally permissive (i.e. all live states can be reached.). This study further proposes a maximally permissive control policy for a subclass of systems of simple sequential processes with resources (S 3 PR) based on the above theory of token distribution pattern of unmarked siphons.